Climate-induced storminess forces major increases in future storm surge hazard in the South China Sea region - M. Wood; I. D. Haigh; Q. Q. Le; H. N. Nguyen; H. B. Tran; S. E. Darby; R. Marsh; N. Skliris; J. J.-M. Hirschi; R. J. Nicholls; N. Bloemendaal (Natural Hazards and Earth System Sciences, 2023)
Coastal floods, driven by extreme sea levels, are one of the most dangerous natural hazards. The people at highest risk are those living in low-lying coastal areas exposed to tropical-cyclone-forced storm surges. Here we apply a novel modelling framework to estimate past and/or present and future storm-surge-level and extreme-sea-level probabilities along the coastlines of southern China, Vietnam, Cambodia, Thailand, and Malaysia. A regional hydrodynamic model is configured to simulate 10 000 years of synthetic tropical cyclone activity, representative of a past/present (1980–2017) and high-emission-scenario future (2015–2050) period. Results show that extreme storm surges, and therefore total water levels, will increase substantially in the coming decades, driven by an increase in the frequency of intense tropical cyclones. Storm surges along the southern Chinese and northern and southern Vietnamese coastlines increase by up to 1 m, significantly larger than expected changes in mean sea-level rise over the same period. The length of coastline that is presently exposed to storm surge levels of 2.5 m or greater will more than double by 2050. Sections of Cambodian, Thai, and Malaysian coastlines are projected to experience storm surges (at higher return periods) in the future, not previously seen, due to a southward shift in tropical cyclone tracks. Given these findings, coastal flood management and adaptation in these areas should be reviewed for their resilience against future extreme sea levels.